Analysis of a Traditional Dhakon Game-Based Learning Model in Preserving Local Wisdom of Fifth Grade Students at SDN 2 Sarimulyo Kemusu - Yuliantika, Ananda Agustin; Handini, Oktiana; Hastini, Dite (FKIP - Universitas Riau, 2025)
This study aims to identify, analyze, and describe the implementation of a learning model based on the traditional game Dhakon as a means of preserving local wisdom among fifth-grade students at SD Negeri 2 Sarimulyo Kemusu. It also explores the supporting and inhibiting factors encountered during the implementation process. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. The research subjects included the principal, the fifth-grade teacher, and selected students, chosen purposively. To ensure data validity, the study utilized triangulation of techniques and sources, increased observational persistence, and references to relevant literature. The findings reveal that the Dhakon-based learning model effectively instills values of local wisdom such as cooperation, sportsmanship, patience, and a love for national culture. The implementation was integrated into thematic learning, character-building activities, and local content lessons. Despite facing challenges such as limited instructional time and lack of supporting media, these issues were addressed through teacher innovation and school-wide collaboration. Thus, the Dhakon traditional game has proven to be an effective educational medium for integrating local cultural values into elementary school learning.